Comparison of The Computer Viruses from Time to Time - Sulianta, Feri (CENTRAL ASIA AND THE CAUCASUS, 2022)
The term Virus was first published academically by Fred Cohen in 1984 in a scientific paper. Computer viruses have a way of working identical to biological viruses in general, so it's no wonder the naming of computer viruses takes the term biology. The main characteristic of a computer virus is that a virus requires a master file to infect when replicating itself, this is what distinguishes computer viruses from other destructive computer programs. Several categories of computer virus are boot virus, program virus, multipartite virus, stealth/polymorphic virus, metamorphic virus and macro virus.The infected master file is called the host file. Today, a computer virus refers to a program that is capable of self-replicating and spreading by duplicating virus codes into the infected file or document.